Groundwater quality zonation by total dissolved solids for Hưng Yên province - Roi, Nguyen Duc (Vietnam Journal of Earth Sciences, 2016)
Hưng Yên province has relatively abudant groundwater (GW) resource, howerver the groundwater quality distribution is variable, including total dissolved solids (TDS). Groundwater zonation by TDS is important for sustainable GW planning in term of quality. Analysis of the TDS spatial distribution for all the three aquifers Holocene (qh), upper Pleistocene (qp2) and lower Pleistocene (qp1) have given variogram of a power type of very high correlation coefficient with the actual data which means a high reliability. TDS kriging had been applied to compile GW zonation by TDS contents in three levels: fresh, light brackish and brackish for the aquigfers qh, qp2 and qp1. The areas of GW of light brackish to brackish area: (i) aquigfer qh: ~310 km2 (~33 % of the area); (ii) aquigfer qp2: ~10 km2 (~23 % of the area); (iii) aquigfer qp1: ~180 km2 (~20 % of the area). The areas of brackish GW of qh and qp2 are very different, which means the two aquifers are of insignificant vertical interaction or no interaction thanks to the aquitard inbetween. The areas of brackish GW of qp2 and qp1 are relatively similar with only lightly difference in shapes, which may be an evidence of good hydraulic interaction between the two aquifer there Based on the combination of GW zonation by TDS and the locations and abstraction quantities of existing GW abstraction facilities, some salinization prevention measures, inluding artificial recharge had been proposed.References Nguyễn Văn Độ (chủ biên), 2002: Đo vẽ lập bản đồ địa chất, địa chất thủy văn - địa chất công trình tỷ lệ 1:50.000 vùng Hưng Yên - Phủ Lý. Lưu trữ Liên đoàn Quy hoạch và Điều tra Tài nguyên nước Miền Bắc, 180tr. Ghislain de Marsily, 1987: Quantitative Hydro-geology: Groundwater Hydrology for Engineers. Academic Press Inc., Harcourt Brace Jovanovich Publishers, pp.284-329. Nguyễn Văn Hoàng, 1998: Phương pháp Kriging và ứng dụng nó để tính hệ số dẫn áp và nồng độ sắt trong nước dưới đất vùng Hà Nội. Tuyển tập các báo cáo khoa học: Hội nghị khoa học lần thứ 13-Trường Đại học Mỏ-Địa chất; Quyển 3, tr.144-149. Nguyễn Văn Hoàng, Nguyễn Đức Rỡi, 2015: Study on the hydraulic connectivity between Holocene and Pleistocene aquifers and the Red river in Hung Yen city area. Tạp chí Khoa học Đại học Quốc gia Hà Nội: Các Khoa học Trái đất và Môi trường; tập 31, số 2, pp.11-22. Kemker Christine, 2014: Conductivity, Salinity and Total Dissolved Solids. Fundamentals of Environmental Measurements. Fondriest Environmental, Inc. 3 Mar 2014. Phạm Quý Nhân (chủ biên), 2007: Báo cáo kết quả thăm dò đánh giá trữ lượng khai thác NDĐ Trung tâm dệt kim Phố Nối công suất 5.000 m3/ng. Lưu trữ Sở TN&MT, Hưng Yên, 135tr. Bộ Tài nguyên và Môi trường, 2008: QCVN 09: 2008/BTNMT- Quy chuẩn kỹ thuật Quốc gia về chất lượng nước ngầm. Lưu trữ Bộ TN&MT, 6tr. Bộ Tài nguyên và Môi trường, 2014: Thông tư số 09/2014/TT-BTNMT: Quy định kỹ thuật lập bản đồ chất lượng nước dưới đất tỷ lệ 1:50.000. Lưu trữ Bộ TN&MT, 6tr. Sở Tài nguyên và Môi trường Hưng Yên, 2014: Báo cáo tình hình khai thác, sử dụng nước tỉnh Hưng Yên năm 2014. Lưu trữ Sở TN&MT, Hưng Yên, 14tr.